2023
DOI: 10.1107/s1600577522009845
|View full text |Cite
|
Sign up to set email alerts
|

A new high temperature, high heating rate, low axial gradient capillary heater

Abstract: A new heater design, capable of fast heating and cooling to and from >1000°C, has been developed at the Swiss–Norwegian Beamlines, European Synchrotron Radiation Facility, France. The design uses a SiC head to distribute heat, and resistive Si3N4 heat cartridges to provide heat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In situ X-ray diffraction measurements up to 930 °C were performed at BM01 (Swiss-Norwegian beamlines (SNBL), European Synchrotron Radiation Facility (ESRF), Grenoble), using a wavelength of 0.60546 Å, a beam size of 240x180 μm 2 and a 2M Pilatus detector (Dectris). The materials were mounted in 0.3 mm quartz capillaries and heated by a custom solid-state heater with a SiC head and Si3N4 resistive heat-cartridge [24]. Heating and cooling rates were 15 °C/min.…”
Section: Methodsmentioning
confidence: 99%
“…In situ X-ray diffraction measurements up to 930 °C were performed at BM01 (Swiss-Norwegian beamlines (SNBL), European Synchrotron Radiation Facility (ESRF), Grenoble), using a wavelength of 0.60546 Å, a beam size of 240x180 μm 2 and a 2M Pilatus detector (Dectris). The materials were mounted in 0.3 mm quartz capillaries and heated by a custom solid-state heater with a SiC head and Si3N4 resistive heat-cartridge [24]. Heating and cooling rates were 15 °C/min.…”
Section: Methodsmentioning
confidence: 99%
“…In situ SXRD measurements were performed at the Swiss Norwegian Beamline (SNBL), BM01, at the European Synchrotron Radiation Facility (ESRF, Grenoble, France) using the PILATUS@SNBL diffractometer ( λ = 0.68966 Å) in a high‐intensity beam mode (≈200 mA). The experiments were conducted under N 2 atmosphere using custom‐made furnace, [ 46 ] which was gradually heated at the ramp rate of 20 °C per min up to 1000 °C. The data acquisition time was 10 s per pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, hard X-ray-based techniques appear very promising due to the possibility of simultaneously obtaining information about the electronic state and the local structure surrounding the adsorbing atom under realistic reaction conditions. For such in situ / operando studies, different cells have been constructed over the past years to mimic realistic reaction conditions. , Concerning the steam reforming of methane, this reaction requires high temperatures (up to 900 °C) even during catalyst activation, and only a few in situ / operando setups exist, which are capable of fulfilling these conditions. For instance, La Fontaine et al recently reported a reaction environment able to reach 1000 °C with various heating/cooling ramp rates, which is suitable also for methane steam reforming studies. Analogous, Eggart et al conducted in situ / operando XAS investigations up to 1000 °C with a newly developed cell.…”
Section: Introductionmentioning
confidence: 99%
“… 34 , 35 Concerning the steam reforming of methane, this reaction requires high temperatures (up to 900 °C) even during catalyst activation, and only a few in situ / operando setups exist, which are capable of fulfilling these conditions. 36 38 For instance, La Fontaine et al 39 recently reported a reaction environment able to reach 1000 °C with various heating/cooling ramp rates, which is suitable also for methane steam reforming studies. Analogous, Eggart et al 38 conducted in situ / operando XAS investigations up to 1000 °C with a newly developed cell.…”
Section: Introductionmentioning
confidence: 99%